Leadership Identity of School Principal : The Performance of Personality - ธนะสีลังกูร จตุรงค์ (Journal for Developing the Social and Community, 2016)
Leadership is based on the life-shaping experiences, learning experiences, There are including to the process of art and science in Leading. It’s constructing to the image of an executive who expresses an Individual Personality. This feature includes the ideas, beliefs, values which determine the behavior management practices in the administration that are typical of its own…